NEEDS ANALYSIS OF ENGLISH FOR SPECIFIC PURPOSES AT POLITEKNIK GIHON - Wiwik Damanik; Erika Sinambela; Arsen Nahum Pasaribu (STKIP Persada Khatulistiwa Sintang, 2021)
The needs analysis cannot be separated from the development of materials and curriculum design for language learning, especially ESP. The research about ESP, especially the topic of need analysis still needs to be explored. Thus, this research aims to identify language skills needed and develop English teaching materials at Politeknik Gihon. The subjects of this study were 45 ongoing students and six former students. The result of the study revealed the perceptions of the students’ needs for their current studies and future career and how the English material should be designed in this institution. This study contributes in developing the teaching material and proposed a redesigned of ESP course.